Field Research in the Operating Room. (October 2016) - Mhlaba, Julie M.; Christianson, Laura W.; Davidson, Stuart J.; Graves, S. Nicholas; Still, Brady R.; Silas, Megan R.; Fong, Abigail J.; Nassiri, Ashley M.; Pariser, Joseph J.; Langerman, Alexander J.
The study of the operating room (OR) began over a century ago and has continued to advance. However, for nonmedical researchers, unique challenges present themselves that must be carefully addressed. We present an overview of the OR aimed at nonmedical researchers interested in studying the OR environment. Based on our extensive experience, we identify several key challenges and describe ways to circumvent them. With a respectable understanding of the OR environment, we can prepare a researcher to gather useful data. Such investigations have the potential to yield great insights about cost savings, efficiency, methods, processes, and general human interaction, among others.